Sistem Kendali Distribusi Gas Buang pada Waste Heat Recovery Power Generation untuk dikonversi menjadi Energi Terbarukan di Indarung V, PT. Semen Padang, Indonesia - Nasrul Harun; Valdi Rizki Yandri (Elektron : Jurnal Ilmiah, 2020)
The coal combustion processes which require high temperature will produce waste heat energy. The energy can be used as generator propulsion to produce electrical energy. Thus, Semen Padang Corporation has successfully got funding from the Japan government, New Energy Technology Development Organization (NEDO) to build the installation Waste Heat Recovery Power Generation (WHRPG) located in the production area of Semen Padang Corporation, Indarung V. Furthermore, heat energy process can not be operated manually, so control system is needed to control this WHPRG performance. The operational of WHPRG can produce electricity power 196.15 MW as to reduce the electric power that must be supplied by Indonesian Electricity Corporation. Besides that, the outcome of Semen Padang Corporation can be saved 33 billion Rupiah per year and CO2 emission can be declined 33,000 tons per year.